Characterization and validation of point mutation in MBL1 gene and its relationship with mastitis in Murrah buffalo (Bubalus bubalis) - Dhundwal, Kamaldeep; Pander, B. L.; Dalal, D. S.; Magotra, Ankit; Mittal, Dinesh; Singh, M.; Malik, Anika; Garg, Asha (Buffalo Bulletin, 2019)
Mannose Binding Lectins (MBL) gene possibly contributes to bacterial infection resistance and was proposed as a molecular marker for milk production traits to control mastitis A total of 60 Murrah buffaloes were selected to characterize exon 2 of MBL1 gene to identify polymorphism and its association with mastitis. A 401 bp PCR fragment of MBL1 gene targeting g.2686T>C was amplified and digested with HaeIII restriction enzyme. Genotype analysis using PCR-RFLP revealed a monomorphic CC banding pattern. Sequencing was also carried out to explore other SNPs. The result indicates highly conserved DNA sequence in Murrah buffalo. This study provides preliminary information that the targeted region of MBL1 gene in water buffalo has no significant association with mastitis resistance which maybe a breed specific characteristic. Since present study has formulated the results based on a relatively small sample, further studies are required to validate these results in large samples.